VD_FINDINFO Jug / 2011 / 219 vom 17. Februar 2011 - VD Tribunal cantonal (2011)
QUALITÉ POUR RECOURIR, PLAIGNANT, ABUS DE CONFIANCE, ACQUITTEMENT, DÉPENS | 138 ch. 1 CP, 126 CPP (CH), 382 al. 1 CPP (CH), 382 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)